EXPERIENCE FORMATION ARTISTIC AND AESTHETIC OUTLOOK TEACHERS OF THE ARTISTIC SUBJECTS IN THE POSTGRADUATE EDUCATION - Solomacha, Svetlana (Continuing Professional Education: Theory and Practice, 2019)
This article reviews new artistic and pedagogical techniques of artistic-aesthetic outlook teachers of artistic disciplines. The author focuses on the pedagogical potential impact of art on the individual, as a powerful ideological tool of cultural identity formation in general and ideological culture of teachers of artistic disciplines, in particular. Because of the impact on the sense of art makes cognitive, aesthetic, hedonistic function that allows you to implement a holistic approach to the development of artistic vision as a necessary component of professional training of teachers and their spiritual growth facto. Thus, the basic fundamental position of art education is the formation of the unity of the spiritual culture of personality, the transition from information to education through art and esthetic relation of man to the world.